2015
DOI: 10.1007/s00601-015-0960-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Tests of the Envelope Theory for Few-Boson Systems

Abstract: The envelope theory, also known as the auxiliary field method, is a simple technique to compute approximate solutions of Hamiltonians for N identical particles in D-dimension. The accuracy of this method is tested by computing the ground state of N identical bosons for various systems. A method is proposed to improve the quality of the approximations by modifying the characteristic global quantum number of the method.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 21 publications
7
46
0
Order By: Relevance
“…Let us first remark that irrelevant values for the energies (complex or positive real numbers) are computed with the ET when the number of particles is too small. Such a behaviour was already observed for D = 3 [7]. The quality of the bound strongly depends on the value of a.…”
Section: Gaussian Potentialsupporting
confidence: 61%
See 2 more Smart Citations
“…Let us first remark that irrelevant values for the energies (complex or positive real numbers) are computed with the ET when the number of particles is too small. Such a behaviour was already observed for D = 3 [7]. The quality of the bound strongly depends on the value of a.…”
Section: Gaussian Potentialsupporting
confidence: 61%
“…The ET has already been tested in the D = 3 space for various Hamiltonians up to 10 bosons [7,8]. It was shown that reliable results can be obtained for energies and some observables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The envelope theory is an efficient and convenient tool to obtain approximate solutions for quantum systems made of N identical particles [7][8][9]. With this method, the quantum energy of N self-gravitating particles with a mass m in D-dimensional space is given by [10]…”
mentioning
confidence: 99%
“…where the quantum period T q and quantum energy E q of N self-gravitating particles with a mass m in Ddimensional space [1,8,9]. For further discussion, we call Eq.…”
Section: Fig 2: N-body Systemmentioning
confidence: 99%